Return of state financial losses corruption criminal acts - Wahyuadi, Bambang; Warka, Made; Hufron, Hufron (Technium Social Sciences Journal, 2023)
In the reform era, in 1999 to be precise, Law Number 31 of 1999 concerning the Eradication of Corruption Crimes was formed, which was later amended and added to in 2001 by forming Law Number 20 of 2001 concerning Amendments to Law Number 31 of the Year 1999 (hereinafter referred to as the Corruption Act). The aim of the Corruption Crime Law is to prevent the loss of state money due to unlawful acts by unlawful state officials, or other parties who benefit. The urgency of returning state finances due to criminal acts of corruption, is caused more by losses as a result of the unlawful acts of the perpetrators. Returning state financial losses does not eliminate corruption. By returning state losses, it has actually been stated that there were state losses that occurred before. In voltooid delict, state losses have existed or occurred if the state losses were desired by the perpetrators of criminal acts. The intention to harm state finances can be seen from the will of perpetrators criminal acts who wish to gain more profit from activities financed with state funds. This excess profit creates a shortage of work carried out resulting in state losses, namely that the amount of money spent is not in accordance with what is spent or there is a shortage of state money spent.